2020
DOI: 10.3389/fmars.2020.537010
|View full text |Cite
|
Sign up to set email alerts
|

Imminent Risk of Extirpation for Two Bottlenose Dolphin Communities in the Gulf of Guayaquil, Ecuador

Abstract: A long-term study of a common bottlenose dolphin (Tursiops truncatus) population inhabiting the Gulf of Guayaquil, Ecuador (2 • 33 S, 79 • 20 W), has been carried out for almost 30 years. Similarly, as in other parts of the world, this population is structured socially and spatially in well-defined subunits or communities. Two of these communities, referred to as Posorja and El Morro, have been studied with major intensity in the last 10 years in the western inner estuary, among others to calculate population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Does the humpback whale, as a flagship species, lead to improved conservation? In interviews, Fernando Felix [47] and Ben Haase [48] indicated that the whale-watching regulation is only useful to the extent that it will be enforced by the authorities. In other words, they believe that conservation ultimately depends on the state's capacity to intervene and implement protective policies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Does the humpback whale, as a flagship species, lead to improved conservation? In interviews, Fernando Felix [47] and Ben Haase [48] indicated that the whale-watching regulation is only useful to the extent that it will be enforced by the authorities. In other words, they believe that conservation ultimately depends on the state's capacity to intervene and implement protective policies.…”
Section: Discussionmentioning
confidence: 99%
“…The tourism operators collaborated by allowing the researchers to record their data while aboard the tourist vessels, which made the relationship mutually beneficial [45,46]. Félix noted that when whale-watching began in the early 1990s, it was the only form of nature-related tourism available on the mainland coast of Ecuador [47]. Ben Haase recalled, "Twenty-five years ago, all the attention was on the Galápagos, nobody knew anything about the [mainland] coast" [48].…”
Section: Collecting Data On the Humpback Whale Populationmentioning
confidence: 99%
See 3 more Smart Citations